2008
DOI: 10.1002/aqc.944
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three types of adhesives in attaching coral transplants to clam shell substrates

Abstract: ABSTRACT1. Nubbins from 12 coral species were transplanted onto dead giant clam shells at three sites in a lagoon near Bolinao, north-western Philippines. Transplants were attached using three types of adhesives: cyanoacrylate glue (SG), epoxy putty (EP) and marine epoxy (ME) and were monitored over five months for detachment, in situ mortality and natural self-attachment by tissue growth.2. Corals attached with SG showed a significantly higher rate of detachment (logrank test) than those attached with either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…This is commonly facilitated with the use of marine epoxy, which easily binds to the skeletal framework of hard coral colonies or fragments and allows them time to selfattach onto the substratum (Dizon et al, 2008). Our trials, however, showed that direct application of epoxy was not feasible for softbodied sponges and soft corals.…”
Section: Discussionmentioning
confidence: 81%
“…This is commonly facilitated with the use of marine epoxy, which easily binds to the skeletal framework of hard coral colonies or fragments and allows them time to selfattach onto the substratum (Dizon et al, 2008). Our trials, however, showed that direct application of epoxy was not feasible for softbodied sponges and soft corals.…”
Section: Discussionmentioning
confidence: 81%
“…For fast growing, highly fragmenting species like members of the Acroporidae and Pocilloporidae, fragmentation and subsequent reattachment is an important life strategy that sometimes determines species' spatial coverage and distribution (e.g., thicket formation; Highsmith, 1982). Attachment may also be a determining factor of coral health as more energy is channelled through growth and formation of new tissue onto the substratum, though attachment time varies with coral species and morphology (Dizon et al, 2008;Guest et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…1 cm in diameter) that were bored using an improvised auger. The corals were attached using Pioneer EpoxyclayAqua, a two-part adhesive that can be mixed underwater by kneading with the fingers (Dizon et al, 2008). The substrate surrounding the holes was scrubbed clean with a steel brush.…”
Section: Transplantation To Experimental Bommiesmentioning
confidence: 99%
“…One aspect of coral transplantation that has yet to be studied comprehensively is the time taken for coral fragments from different species to self‐attach to substrata following fragmentation and transplantation. For reef restoration, coral transplants are sometimes scattered on areas of bare reef (Bowden‐Kerby 1997) or more commonly fragments are artificially attached or stabilized using marine epoxy, cyanoacrylate glue (Dizon et al 2008), cement (Ortiz‐Prosper et al 2001), polythene string (Lindahl 2003), cable ties or stainless‐steel wire (Bruckner & Bruckner 2001). These methods can be very effective in the short term and attached or stabilized coral fragments tend to survive better than unattached fragments (Bowden‐Kerby 1997; Lindahl 2003).…”
Section: Introductionmentioning
confidence: 99%